Rising mortality related to cardiovascular disease and prostate cancer amongst older men across the United States - Abdul Ahad (545575) (2024)
Objective There is a significant association between cardiovascular diseases (CVD) and prostate cancer (PCa), leading to high mortality. This study evaluates the trends in mortality associated with CVDs and PCa among older (≥ 65 years) men in the United States (US). Methods This analysis utilized the Centers for Disease Control and Prevention's Wide-Ranging Online Data for Epidemiologic Research (CDC WONDER). The analysis of Multiple Cause of Death Files was carried out from 1999 to 2019 to identify fatalities with CVD and PCa listed as either contributory or underlying causes of death. Crude and age-adjusted mortality rates (AAMRs) per 100,000 populations for variables such as year, race and ethnicity, and geographic regions were determined. To assess annual percent change (APC), a Joinpoint regression program was employed. Results Overall AAMR was 54.3 in 1999 and 34.6 in 2019. After a decline in AAMR from 1999 to 2015, an alarming rise in mortality was observed until 2019. Mortality rates were highest among Non-Hispanic (NH) Black and African American men (74.9). Geographically, the highest mortalities were witnessed in the West (46.4) and non-metropolitan areas (44.6). States with AAMRs ranking in the 90th percentile were Nebraska, California, North Dakota, the District of Columbia, and Mississippi. Conclusion After decreasing death rates associated with CVD and PCa from 1999 to 2015, a reversal in the trend was observed from 2015 to 2019. Addressing this increase in death rates, especially among the vulnerable population, requires focused attention and targeted strategies to implement necessary safeguards in the upcoming years. Other Information Published in: Current Problems in Cardiology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.cpcardiol.2024.102785